General Strategies in Developing Alloy Steel Fuzzy Model for Machinability Data Selection of Turning Process - Tan, J. Y.; Wong, Shaw Voon; Ismail, Napsiah; Salem Hamouda, Abdel Magid (Universiti Putra Malaysia Press, 2004)
In this paper, several fuzzy models have been proposed for machinability data selection of turning process of alloy steel. The selection of the machinability data is a crucial task, and normally done by the skilled machinists. Thus, fuzzy models-have been suggested for predicting the optimum machinability data, which are cutting speed and feed rate. These fuzzy models are developed based on the relationship of two-input (material hardness and depth of cut) and two-<>utput (cutting speed and feed rate). A few general strategies in developing fuzzy models are presented and discussed in this paper. Generally, there are three different strategies that are suggested in this paper. The objective of implementing these strategies is to simplify the process of fuzzy model development. The predicted cutting speed and feed rate are compared with the data obtained from the Machining Data Handbook (Metcut Research Associate 1980) and a good correlation has been shown throughout the comparison.